SISTEM INFORMASI PERSEDIAAN BARANG DENGAN SAFETY STOCK - alzena sabilla; Danang Mahendra (Journal of Information System and Computer, 2022)
Inventory is important for a business. Fashion has a dynamic environment. At any time highdemand makes SMEs stockout of inventory so they cannot fulfill the demand. SMEs must have astrategy to facilitate running business processes such as automation by utilizing technology. In thiscase, the inventory system is one solution to overcome problems in inventory in order to fulfillconsumer needs. This application uses the safety stock method to find out the safe stock that must beavailable with fluctuating demand. This research resulted in a web-based inventory information systemapplication that can reduce the amount of inventory and demand for goods so as to improve servicesoptimally and effectively